Morphology, Biometry, and Taxonomy of Freshwater and Marine Interstitial Cyphoderia (Cercozoa: Euglyphida) - Todorov, Milcho; Golemansky, Vassil; Mitchell, Edward; Heger, Thierry J. (My University, 2009)
Good taxonomy is essential for ecological, biogeographical, and evolutionary studies of any group of organisms. Therefore, we performed detailed light- and scanning electron microscopy investigations on the shell ultrastructure and biometric analyses of the morphometric variability of five freshwater and marine interstitial testate amoebae of the genus Cyphoderia (C. trochus var. amphoralis, C. ampulla, C. margaritacea var. major, C. compressa, and C. littoralis), isolated from different populations in Bulgaria and Switzerland. Our aims were (1) to clarify the morphological characteristics of these taxa, and (2) to compare the morphology of a given taxon (C. ampulla) among different locations in Bulgaria and Switzerland as a first step towards an assessment of the geographical variation within a supposedly cosmopolitan taxon. Four of the studied taxa are characterized by a well-expressed main-size class and by a small size range of all the characters and can be defined as size-monomorphic species. Based on these results, the following systematic changes are proposed: C. major (Penard, 1891) n. comb. (Syn.: C. margaritacea var. major (Penard, 1891) and C. amphoralis (Wailes & Penard, 1911) n. comb. (Syn.: C. trochus var. amphoralis (Wailes & Penard, 1911)). However, we also show significant morphological variability between the Swiss and Bulgarian populations of C. ampulla, suggesting the possible existence of more than one taxon within this species. Further studies are required to assess (1) if these two morphologically different taxa represent individual species, (2) if so, if more species exist, and if this diversity is due to limited distribution ranges (endemism) or if several closely related taxa occur together in different geographical areas.
Keywords: Biometry; Cyphoderia; Cyphoderia amphoralis n.comb.; Cyphoderia major n.comb.; morphology; taxonomy; testateamoebae